Investigating seasonal variation in abdominal fat indices and hypertension amongst Ellisras population from childhood into adulthood : Ellisras Longitudinal Study - Mkhatshwa, Thandiwe Ntomfuthi (My University, 2024)
Background: Obesity and hypertension have been a global concern, affecting both developing and developed countries. Studies reported seasonal variation as a common risk factor for the development of obesity and blood pressure (BP). However, studies that investigated seasonal variation in obesity and BP over time remain scanty, especially in developing countries. Aim and objectives: This study was aimed at investigating seasonal variation in obesity and BP among the Ellisras population aged 4−18 years over time. Furthermore, the study investigated whether there is an association between autumn and spring obesity and BP variables among the Ellisras population during a specific period. The study also investigated whether there is a risk associated with the development of obesity and BP (hypertension) between autumn and spring variables among the Ellisras population over time. Methods: This study forms part of the Ellisras Longitudinal study, of which data was sourced. Anthropometric measurements were measured following the procedure by the International Society for the Advancement of Kinanthropometry. Blood pressure measurements were measured following the procedure by the National High Blood Pressure Education Program (NHBPEP) Working Group on Hypertension Control in Children and Adolescents. At baseline, measurements were collected in the autumn of 1999 with 1 974 (1033 boys and 941 girls) participants. The same participants were followed repeatedly over time (autumn and spring 2000, 2001, 2003). In spring 2003, a total of 1 701 (873 boys and 828 girls) participants were still present in the study. Frequency analysis was used to determine the prevalence of obesity, elevated BP and hypertension in autumn and spring. The generalised estimating equation (GEE) was used to investigate the seasonal association in abdominal fat indices and BP variables in autumn and spring. Furthermore, GEE was used to investigate the risk associated with the development of obesity and BP (hypertension) in autumn and spring during that period. Results: The results showed that the prevalence of obesity by waist circumference (WC) was mostly markedly (P≤0.05) higher in autumn (0−30.4%) than spring (0−26.9%) among Ellisras boys and girls aged 4−18 years from 1999−2003. Furthermore, the prevalence of vi obesity by waist-to-height ratio (WHtR) was mostly significantly (P≤0.05) higher in autumn (0−20.8%) than spring (0−1.3%) among Ellisras boys and girls from 2000−2002. In addition, the prevalence of obesity by waist-to-hip ratio (WHR) was mostly significantly higher in autumn (21.5−95.5%) compared to spring (13.1−88.9%) among Ellisras boys and girls from 1999−2003. Diastolic BP showed the weakest significant (P≤0.05) association (B=0.007, 95% CI: 0.000−0.012) between baseline measurements (autumn 1999) and subsequent spring (1999−2003) measurements when adjusted for age and gender. The strongest significant (P≤0.05) association was observed in WHR (B=0.096, 95% CI: 0.077−0.116) between baseline measurements (autumn 1999) and subsequent spring (1999−2003) measurements. However, in autumn 2003 only WC (B=0.075, 95% CI: 0.056−0.094) and systolic BP (B=0.009 95% CI: 0.003−0.016) were still substantially (P≤0.05) associated with spring measurements (1999−2003) when adjusted for age and gender. Furthermore, WC showed the weakest substantial (P≤0.05) risk (OR=0.003, 95% CI: 0.002−0.011) between baseline measurements (autumn 1999) and subsequent spring measurements (1999−2003) when unadjusted for age and gender. The strongest significant (P≤0.05) risk was observed in obesity by WHtR (OR=0.619, 95% CI: 0.554−0.683) between baseline measurements (autumn 1999) and subsequent spring (1999−2003) measurements when unadjusted for age and gender. In autumn 2003, only systolic BP showed a substantial (P≤0.05) risk (OR=0.036, 95% CI: 0.016−0.057) and (OR=0.033, 95% CI: 0.014−0.054) both unadjusted and adjusted for age and gender respectively. Conclusion: Seasonal variation in abdominal fat indices and BP was evident in this population of boys and girls and it differs by age group. A significant association between autumn and spring measurements for obesity and BP variables was evident in this study for that period. Furthermore, the development of obesity and BP is associated with seasons.
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 2024
Keywords: Seasonal variation; Blood pressure; Obesity; Ellisras; South Africa; Hypertension -- South Africa -- Limpopo; Health and Wellbeing -- South Africa -- Limpopo Province; Obesity -- Social aspects; Abdomen